SARS-CoV-2 vaccine research and development: conventional vaccines and biomimetic nanotechnology strategies (2020)
The development of a massively producible vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus, is essential for stopping the current coronavirus disease (COVID-19) pandemic. A vaccine must stimulate effective antibody and T cell responses in vivo to induce long-term protection. Scientific researchers have been developing vaccine candidates for the severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) since the outbreaks of these diseases. The prevalence of new biotechnologies such as genetic engineering has shed light on the generation of vaccines against novel viruses. In this review, we present the status of the development of coronavirus vaccines, focusing particularly on the biomimetic nanoparticle technology platform, which is likely to have a major role in future developments of personalized medicine.